PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, PERTUMBUHAN PENJUALAN, LEVERAGE OPERASI DAN KEPEMILIKAN MANAJERIAL TERHADAP STUKTUR MODAL - Naila Rahmah, 09.05.51.0039; Irsyad, Moch. (Students Journal of Economic and Management, 2013)
This study aimed to examine the influence of Asset Structure, Profitability, Sales Growth, Operating Leverage and Managerial Ownership on capital structure in companies that went public in Manufacturing IndonesiaStock Exchange. The population in this study is a manufacturing company on the Stock Exchange in 2008-2010 as many as 143 per year. The samples used in this research is a group of manufacturing companies with certain criteria. The number of samples obtained by the study criteria that have been determined are 153 companies. This data was obtained from the Indonesia Stock Exchange Corner Stikubank University. The analytical tool used in this study is multiple linear regression using the t test and the Test F. The results of this study: The F in this study showed all the independent variables (the structure of assets, ROA, sales growth, operating leverage and managerial ownership) jointly significant effect on the capital structure with a significance level of 0.000 < 0.05. While the t-test on each of the independent variables showed that variables that have a significant effect on the capital structure of Profitability, Growth and Managerial Ownership. And variables that do not have a significant effect on the capital structure of the Variable Structure Leverage Assets and Operations. The independent variable (Structure Assets, Profitability, Sales Growth, Operating Leverage and Managerial Ownership) can explain the capital structure of 15.60% while the sides are explained by other factors not observed.Key words: Structure of Assets, Profitability, Sales Growth, Operating Leverage and Managerial Ownership.